1985
DOI: 10.1002/em.2860070207
|View full text |Cite
|
Sign up to set email alerts
|

Increased mutagenicity of chromium compounds by nitrilotriacetic acid

Abstract: Nitrilotriacetic acid trisodium salt (NTA), which is a substitute for polyphosphates in household laundry detergents, and N-nitrosoiminodiacetic acid (NIDA), a derivative of NTA produced by metabolism of soil microorganisms, were tested for in vitro mutagenicity in bacteria and yeasts. No gene reversions in five strains of Salmonella typhimurium (TA 1535, TA1537, TA1538, TA98, and TA100), no forward gene mutations in Schizosaccharomyces pombe P1, and no mitotic gene conversions at two loci in Saccharomyces cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…These results are in agreement with the literature [Loprieno et al, 1985;Zeiger et al, 1992]. Regarding results obtained in the presence of S9-mix, the lack of mutagenicity was noticed when using either liver or kidney rat microsomal fractions.…”
Section: Discussionsupporting
confidence: 95%
“…These results are in agreement with the literature [Loprieno et al, 1985;Zeiger et al, 1992]. Regarding results obtained in the presence of S9-mix, the lack of mutagenicity was noticed when using either liver or kidney rat microsomal fractions.…”
Section: Discussionsupporting
confidence: 95%
“…With the exception of monovalent insoluble Hg (as HgCI), we chose the soluble and insoluble salts of divalent Cd, Hg, Ni and Pb for a study of the interaction of heavy metal compounds with NTA in the induction of genetic and chromosomal effects by means of the Sulmonellaimicrosome assay and the SCE test in the CHO mammalian cell line. We had already observed an enhancement of both the frequency of mutations and SCE induced by insoluble Cr(V1) compounds in the presence of NTA [Loprieno et al, 1985;Venier et al, 19851. In the present study, we used the SCE test to investigate the interaction of NTA with metal compounds in the induction of chromosomal effects in mammalian cells.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, it was considered as an indirect nonmutagenic carcinogen, and its occasional clastogenic effects were attributed to nonspecific toxicity caused by the high active concentrations [Brusick, 19801. However, we have already observed that NTA enhances the direct rnutagenicity of several insoluble or scarcely soluble Cr(V1) compounds (Pb, Ba, Sr, Zn, and Ca chromates) in S typhimuriurn, and their ability to induce sister chromatid exchanges in CHO cells [Loprieno et al, 1985;Venier et al, 19851. The same was observed with some industrial pigments containing insoluble Pb and Zn chromates [Venier et al, 19851.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…18 " 20 Metal toxicity and genotoxicity are influenced by environmental factors, among which are the pH, the inorganic ion composition, and the type and concentration of chelating agents. 21 We have shown that the interaction of nitrilotriacetic acid (NTA) with insoluble Cr(VI) compounds causes an increase in the induction of gene mutations in S. typhimurium 22 ' 23 and SCE in cultured mammalian cells. 23 NTA also increases the ability of insoluble compounds of Cd(II), Hg(I), Ni(II) and Pb(II) to induce SCE in cultured hamster CHROMOSOMAL EFFECTS OF NTA-METALS 185 cells while apparently it does not affect the induction of SCE by soluble metal compounds.…”
Section: ' 15~17mentioning
confidence: 99%